PENGARUH TINGKAT HUTANG DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK PADA INDEKS INFOBANK15 - Martcelina Utami Sinaga; Francis Hutabarat (Fakultas Ekonomi Universitas Advent Indonesia, 2023)
This study aims to determine the effect of debt levels (DER) and profitability (ROA) on tax aggressiveness (ETR). The population in this study was obtained using the proposive sampling method for banks in the Infobank Index15 during the 2020-2021 period. There were 28 research samples because 1 bank found incomplete data processing. Statistical analysis using the SPSS application tool in carrying out correlation coefficient analysis, descriptive statistics, determination test, F test, t test, and linear regression analysis. The results showed that the debt level variable had a significant effect and profitability had no significant effect on tax evasion with a regression coefficient of 0.01 and 0.69 respectively and a significance level of 0.017 and 0.421 respectively at the 5% significance level.